2003
DOI: 10.1021/om030459c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of CO Migratory Insertion Reactions with Group 10 Metal−Alkyl and −Alkoxide Bonds

Abstract: The results of density functional calculations on the alternative migratory insertion reactions of CO with the M−OMe and M−Me bonds of group 10 M(Me)(OMe)(PH3)2 model systems are reported. For all three metals insertion into the M−OMe bond to form methoxycarbonyl products is thermodynamically favored over insertion into the M−Me bond to give acyls. This preference is small when M = Ni (ΔΔE R = 3 kcal/mol) but increases down the triad and becomes significant for M = Pt (ΔΔE R = 12 kcal/mol). Both associative fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 64 publications
5
36
1
Order By: Relevance
“…This result is in agreement with the equilibrium between cis and trans species observed by NMR spectroscopy 8. For phenyl migration we considered a three‐centre mechanism16b and located transition state TS2 a‐3 a with an energy barrier of 11.1 kcal mol −1 and the phenyl group migrating in the plane of the complex (see Figure 1). Both the energy and the geometry closely resemble those recently calculated for trans ‐[PdPh(CO)(OEt)(PMe 3 )] by Lei et al 16a.…”
Section: Resultssupporting
confidence: 84%
“…This result is in agreement with the equilibrium between cis and trans species observed by NMR spectroscopy 8. For phenyl migration we considered a three‐centre mechanism16b and located transition state TS2 a‐3 a with an energy barrier of 11.1 kcal mol −1 and the phenyl group migrating in the plane of the complex (see Figure 1). Both the energy and the geometry closely resemble those recently calculated for trans ‐[PdPh(CO)(OEt)(PMe 3 )] by Lei et al 16a.…”
Section: Resultssupporting
confidence: 84%
“…Independently of the participation of the oxygen electron pairs, the carbonylation mechanisms of M-OR bonds in squareplanar d 8 metal complexes resembles the situation for similar alkyls, clearly favoring an associative pathway with a 5coordinate carbonyl intermediate for Ni, and 4-coordinate intermediates for Pd and Pt. [80] Further DFT studies on more realistic [Ni(Me)(OR)(HN=CHCH=NH)] and [Pt(Me)(OR) (PH 2 CH 2 CH 2 PH 2 )] models confirmed the main predictions from the above study and showed the influence of the OÀ R group on the thermodynamic balance of the reaction, the carbonylation of the MÀ O bonds becoming thermodynamically disfavored when OR is an aryloxide group. [81] The widespread application of pincer ligands in the 1990's opened new opportunities in the study of the fundamental reactivity of NiÀ OR and PdÀ OR bonds.…”
Section: Nucleophilicity and Insertion Chemistrysupporting
confidence: 65%
“…[79] Computational (DFT) analysis of the mechanism of CO insertion in simplified Group 10 models of the type [M(Me)(OMe)(PH 3 ) 2 ] (M=Ni, Pd, Pt) confirmed that CO insertion into the MÀ OMe bonds proceeds through the migratory mechanism. [80] Insertion in the MÀ OMe bond is thermodynamically favored over the MÀ CH 3 , although the balance in favor of the MÀ OMe insertion decreases in the order Pt (12 Kcal · mol À 1 ) > Pd (7 Kcal · mol À 1 ) > Ni (3 Kcal/mol). The energy barriers for CO insertion, either in the MÀ C or MÀ O bonds are significant only for Pt, and much lower for Pd and Ni.…”
Section: Nucleophilicity and Insertion Chemistrymentioning
confidence: 98%
“…This ion arises by nucleophilic attack of the alkoxide ion to the carbon atom of one carbonyl ligand giving rise to a C(O)OR group (Macgregor & Neave, ). This reaction is characterized by rapid kinetics and large equilibrium costant (Gross & Ford, ).…”
Section: Characterization Of Alkoxides By Mass Spectrometrymentioning
confidence: 99%